1990
DOI: 10.1126/science.2296719
|View full text |Cite
|
Sign up to set email alerts
|

Priming and Human Memory Systems

Abstract: Priming is a nonconscious form of human memory, which is concerned with perceptual identification of words and objects and which has only recently been recognized as separate from other forms of memory or memory systems. It is currently under intense experimental scrutiny. Evidence is converging for the proposition that priming is an expression of a perceptual representation system that operates at a pre-semantic level; it emerges early in development, and access to it lacks the kind of flexibility characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

86
1,512
9
57

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,349 publications
(1,664 citation statements)
references
References 80 publications
86
1,512
9
57
Order By: Relevance
“…Thus, these brain areas are likely to be involved specifically in the comprehension of distorted speech rather than in speech comprehension in general. Interestingly, bilateral activations within the ACC, the FP, and in the frontal operculum have been associated with the retrieval mode in which incoming sensory information is treated as a “retrieval cue” for information stored in episodic memory (Lepage, Ghaffar, Nyberg, & Tulving, 2000; Tulving & Schacter, 1990). The retrieval mode has been shown to become activated in old‐new recognition judgments on whether an item has been previously presented (Lepage et al., 2000; Tulving et al., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these brain areas are likely to be involved specifically in the comprehension of distorted speech rather than in speech comprehension in general. Interestingly, bilateral activations within the ACC, the FP, and in the frontal operculum have been associated with the retrieval mode in which incoming sensory information is treated as a “retrieval cue” for information stored in episodic memory (Lepage, Ghaffar, Nyberg, & Tulving, 2000; Tulving & Schacter, 1990). The retrieval mode has been shown to become activated in old‐new recognition judgments on whether an item has been previously presented (Lepage et al., 2000; Tulving et al., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Explicit memories (also called declarative memory) refer to the learning and memory of facts and events that require conscious recall (Tulving and Schacter, 1990). Explicit learning occurs within conscious awareness and with relatively little experience (Breese et al, 1989;Sharp et al, 1985).…”
Section: Acetylcholine and Explicit Memorymentioning
confidence: 99%
“…In light of this background, the mere exposure effect falls into the same broad implicit memory category as perceptual priming, that is, the facilitation of or bias in the processing of a stimulus as a function of a recent encounter with that stimulus (Butler & Berry, 2004;Seamon et al, 1995). To explain this kind of implicit-explicit dissociation, some authors have proposed that perceptual priming may be mediated by a memory system (e.g., perceptual representation system or procedural memory system) separate from the system that mediates explicit memory (e.g., episodic or declarative memory system) (Cohen & Squire, 1980;Graf & Schacter, 1985;Seamon et al, 1995;Squire, 1992;Tulving & Schacter, 1990). Along these lines, it has been shown that in AD the extrastriatal cortex -where reduced activation is often associated with perceptual priming in the visual modality -remains considerably less prone to neurofibrillary tangle formation than the multimodal association and limbic cortices, which are known to be critical to the memory system that mediates explicit memory performance (Arnold, Hyman, Flory, Damasio, & Van Hoesen, 1991;Pietrini et al, 1999).…”
Section: Introductionmentioning
confidence: 99%